Characterization of amylose inclusion complexes using electron paramagnetic resonance spectroscopy. (September 2018) - Kong, Lingyan; Yucel, Umut; Yoksan, Rangrong; Elias, Ryan J.; Ziegler, Gregory R.
Abstract: Amylose is well known to form inclusion complexes with various small molecules including fatty acids. In this study, we prepared amylose inclusion complexes with stearic acid derived spin probes and demonstrated the electron paramagnetic resonance (EPR) spectroscopy as an emerging tool for studying the microstructure and microenvironment of amylose-guest inclusion complex. Two spin probes, namely 5-doxyl-stearic acid (5-DSA) and 16-doxyl-stearic acid (16-DSA), were used as guest molecules in forming amylose-guest inclusion complexes. The molecular dynamics and local polarity of the spin probes and their interaction with amylose in physical mixtures and inclusion complexes were studied using EPR spectroscopy. Complexed guest spin probes could be released when the inclusion complex was dissolved dimethyl sulfoxide (DMSO) and detected by EPR. Since the inclusion complex could not be dissolved in water, the motion of spin probes was restricted in hydrated samples shown by the powder-like slow spectra. Our findings also indicated that the individual association between amylose and the two DSA molecules in forming the inclusion complexes were different. A portion of 16-DSA molecules were not tightly immobilized in the amylose helical channel, but instead were loosely entrapped in the amorphous region of the semicrystalline V6 -type amylose. Therefore, EPR spectroscopy provides valuable information on the molecular dynamics and microenvironment of guest molecules and their interaction with amylose in inclusion complex, and can be exploited as a useful tool to study amylose-guest inclusion complex and other host-guest systems. Graphical abstract: Image 1 Highlights: Amylose inclusion complexes with stearic acid derived spin probes were synthesized. Molecular dynamics and microenvironment of probes were studied by EPR spectroscopy. EPR evidenced difference in organization of two probes in inclusion complex.